Helping Mom Help Baby: Nutrition-Based Support for the Mother-Infant Dyad During Lactation - Ford, Erin L.; Underwood, Mark A.; German, J. Bruce (Frontiers in Nutrition, 2020)
Lactation and breastfeeding support the short- and long-term health of both mother and infant, yet the success of these processes depend upon individual and combined factors of the pair. Complications during pregnancy and delivery greatly affect the likelihood that a mother will be capable of breastfeeding for at least the recommended six months. Guidelines for women regarding postpartum diet and lifestyle management also fail to reflect the diversity of mother-infant pairs and their circumstances. In our analysis of the literature, we have identified a categorical deficit in modern scientific discourse regarding human lactation; namely, that postpartum involves full-body contribution of resources and thus requires the application of nutrition from a systemic perspective.